Roundtable Report - Gagne, Marylene; Agate, Daniel (Future of Work Institute, 2024)
In July of 2024, our research team held “roundtable” discussions with 40 industry representatives from Australia, Canada, Europe, and the United States to better understand the organisational design issues present in today’s volatile, uncertain, complex, and ambiguous (VUCA) world of work. Participants held various positions including top or senior positions in organisational development, human resource management across various sectors of activity including banking, education, healthcare, government, and resources.